The Small Rho GTPases Rac1 and Rac2 Are Important for T-Cell Independent Antigen Responses and for Suppressing Switching to IgG2b in Mice - Gerasimčik, Natalija; He, Minghui; Dahlberg, Carin I. M.; Kuznetsov, Nikolai V.; Severinson, Eva; Westerberg, Lisa S. (Frontiers in Immunology, 2017)
The Rho GTPases Cdc42, Rac1, and Rac2 coordinate receptor signaling to cell adhesion, migration, and proliferation. Deletion of Rac1 and Rac2 early during B cell development leads to failure in B cell entry into the splenic white pulp. Here we sought to understand the role of Rac1 and Rac2 in B cell functionality and during the humoral antibody response. To circumvent the migratory deficiency of B cells lacking both Rac1 and Rac2, we took the approach to inducibly delete Rac1 in Rac2-/- B cells in the spleen (Rac1BRac2-/- B cells). Rac1BRac2-/- mice had normal differentiation of splenic B cell populations, except for a reduction in marginal zone B cells. Rac1BRac2-/- B cells showed normal spreading response on antibody-coated layers, while both Rac2-/- and Rac1BRac2-/- B cells had reduced homotypic adhesion and decreased proliferative response when compared to wildtype B cells. Upon challenge with the T-cell independent antigen TNP-LPS, Rac1BRac2-/- mice showed reduced antibody response. In contrast, in response to the T-cell dependent antigen sheep red blood cells, Rac1BRac2-/- mice had increased serum titers of IgG1 and IgG2b. During in vitro Ig class switching, Rac1BRac2-/- B cells had elevated germline 2b transcripts leading to increased Ig class switching to IgG2b. Our data suggest that Rac1 and Rac2 serve an important role in regulation of the B cell humoral immune response and in suppressing Ig class switching to IgG2b.